Shamba Shape Up Series 13: Impact of viewing on farmers' knowledge, attitude and practices - Makau, Charles; Alliance of Bioversity International and CIAT (2023)
-Population projections for SSU 13 shows that the programme is estimated to have reached over 8-9 million viewers every week. • More than a third (37%) of the women interviewed said that they are involved in decision making on farming activities. • The Swahili version is the most popular version of the programme. Slightly more than half of respondents (55%) said that they watch the Swahili version only. 21% of respondents said that they watched the English version only. 24% of the respondents said that they watch both versions of the programme. • There is a small number of people who are watching the programme online (2% of respondents). This an important channel since the viewers do not have to watch at a specified time, data from the YouTube analytics show an average of 2,469 views per each episode. • Around 9% of viewers say that have signed up to iShamba, which is in line with the iShamba subscription base of 550,000 sign ups. • Findings from the youth segment show very positive mindset about agriculture: 87% said they would like to engage in it as a business, while three quarters (75%) said they would change the crops /livestock they are currently growing or keeping. Interestingly 92% of those who are not currently farming on their own other than the household farms said that they would like to start farming in the next 3 years. One key area that needs improvement is record keeping as only half (51%) of respondents aged 18-35 said they keep records. vii | P a g e • In future, the content of Shamba Shape Up could include topics on market access (52%), especially for the young viewers, there is an urge to transform agriculture from subsistence to more of a business venture.